Description of Students’ Problem in Learning Toward an Assessment - Sumarni, Akbar Aswin, dan Raudah Mahmud (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2019)
Alternative assessment as a part of the evaluation is an important part ofthe learning cycle and it is believed involving the need either student orteacher in teaching and learning process. This paper s eeks theimpl ementat ion of s el f as s es sment to obtain students' learningperceptions and the effectiveness of autonomous learning in an any fieldstudies. The instruments used for the survey is a self-made questionnairebased on literature review. At the beginning, questionnaire were delivered tostudents in order to get primary students’ reflection of various activities asthey are in any field studies - before seeking information was widely involvedin an interview of 5 students. The results of this study reveal that manyopportunities underlining evaluation come up on surface to classroomdisplaying students’ need and this study is also possible as studentsteachers’reflection what suppose they want to get in learning process. Afurther most of students agreed that many approaches appear in some waysas results of various exercises. As a conclusion we state that selfassessment as a part of alternative assessment can play significant roleby providing wider input into the e f f e c t i v e implementation learningprocess in any field study.